Interconnectivity among assessments from rating agencies: using cluster and correlation analysis - Krejčíř, Jaroslav; Dostál, Petr; Doubravsky, Karel (Business: Theory and Practice, 2014)
The aim of this paper is to determine whether there is a dependency among leading rating agencies assessments. Rating agencies are important part of global economy. Great attention has been paid to activities of rating agencies since 2007, when there was a financial crisis. One of the main causes of this crisis was identified credit rating agencies. This paper is focused on an existence of mutual interconnectivity among assessments from three leading rating agencies. The method used for this determines is based on cluster analysis and subsequently correlation analysis and the test of independence. Credit rating assessments of Greece and Spain were chosen to the determination of this mutual interconnectivity due to the fact that these countries are most talked euroarea countries. The significant dependence of the assessment from different rating agencies has been demonstrated.